DINAMIKA SOSIAL KEDUDUKAN PEREMPUAN DI ARAB SAUDI ERA RAJA SALMAN - Nurul Fajar; Rasyidah Rasyidah (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2021)
This paper discusses the social dynamics of the position of women in Saudi Arabia during the reign of King Salman. In Islam, the concept of brotherhood towards all humans is the same regardless of gender, because in Islam women also have a major role in various aspects of society. Saudi Arabia is one of the Islamic countries that has so far distinguished the rights and positions between men and women. This paper argues that there was a very significant cultural change in Saudi Arabia in the era of King Salman, one of which was related to the position of women in Saudi Arabia. This change occurred due to the rapid development of communication and information technology which made globalization flow in Saudi Arabia. Therefore, there have been many cultural changes, especially regarding the position of women, which Saudi Arabian women have long dreamed of. Cultural changes or modernization in Saudi Arabia are reasonable to do to maintain the Saudi Arabian economy from the threat of a financial deficit.